Clinical implication of blood glucose monitoring in general dental offices: the Ehime Dental Diabetes Study. Issue 1 (13th November 2015) - Harase, Tadahiro; Nishida, Wataru; Hamakawa, Tomohiro; Hino, Satoshi; Shigematsu, Kenji; Kobayashi, Satoru; Sako, Hirofumi; Ito, Shirou; Murakami, Hajime; Nishida, Kei; Inoue, Hiroshi; Fujisawa, Masahito; et al.
Abstract : Objective: We examined whether general dentists can contribute to the detection of patients with undiagnosed diabetes and prediabetes by monitoring blood glucose in dental clinics. Research design and methods: A total of 716 patients who visited clinics for dental treatment were enrolled and classified into 3 groups (mild, moderate, and severe) according to Kornman's criteria for periodontitis. The correlations between the casual blood glucose level, presence or absence of the history of diabetes, and/or severity of periodontitis were evaluated. Results: 68 patients (9.5%) had hyperglycemia (blood glucose ≥200 mg/dL). Of these patients, 20 (29.4%) did not have a history of diabetes. Blood glucose tended to be higher with greater periodontitis severity. Of the 3 groups, the severe periodontitis group had the highest proportion of patients with hyperglycemia (p<0.0001). Conclusions: Patients with dental problems could be screened for diabetes, especially undiagnosed diabetes. General dentists could function as practitioners to screen for diabetes. Trial registration number: UMIN-CTR 000014877.